2006
DOI: 10.1007/s00134-005-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal suction by closed system without daily change versus open system

Abstract: CTSS without daily change is the optimal option for patients needing tracheal suction longer than 4 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 29 publications
2
74
0
2
Order By: Relevance
“…A single investigator reviewed these abstracts, and 48 Number with ventilator-LOS [ Table 4]. The duration of mechanical one study [28] contributed substantially (93%) [25] 2000 France Y/N Stericath ® Randomly Nil Yes 4 NA NA allocated Zeiuton [26] 2003 Brazil Y/Y NA Alternate day Nil Yes 4 NA NA Randomization Rabitsch [28] 2004 Austria Y/Y Trachcare™ Randomized Yes Yes 7 8 8 (sealed envelopes) Topeli [29] [24] and in one study cost was numbers precluded multi-variate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A single investigator reviewed these abstracts, and 48 Number with ventilator-LOS [ Table 4]. The duration of mechanical one study [28] contributed substantially (93%) [25] 2000 France Y/N Stericath ® Randomly Nil Yes 4 NA NA allocated Zeiuton [26] 2003 Brazil Y/Y NA Alternate day Nil Yes 4 NA NA Randomization Rabitsch [28] 2004 Austria Y/Y Trachcare™ Randomized Yes Yes 7 8 8 (sealed envelopes) Topeli [29] [24] and in one study cost was numbers precluded multi-variate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Each way of suctioning was consecutively applied for one month period and one or one and half month of wash out period was interposed between each method. Lorente et al argued that closed tracheal suction system, when it was used for more than 24 hr, does not increase VAP 17 . Therefore, we decided to change the close suction catheter every 48 hrs.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in the exogenous pneumonia rate could be due to the fact that CTSS avoids direct manipulations of the aspiration catheter, as it is protected by a plastic envelope. Nevertheless, in two recent randomised studies, no significant differences were found between the patients suctioning with CTSS or OTSS in terms of either total VAP incidence or exogenous VAP incidence [104,105]. Thus, the evidence does not support the routine use of CTSS for prevention of VAP.…”
Section: Closed Tracheal Suctioning System Versus Open Tracheal Suctimentioning
confidence: 93%
“…For these reasons, CTSS is presumed to offer advantages over OTSS, such as lower gasometric and haemodynamic impairment during the suction of respiratory secretions, which has been found in several studies [94][95][96][97], and a protective effect against VAP, although this latter finding is controversial because only one study has reported a lower incidence of VAP using CTSS [98]. Several other studies have not found significant differences in the incidence of VAP between the systems [99][100][101][102][103][104][105].…”
Section: Closed Tracheal Suctioning System Versus Open Tracheal Suctimentioning
confidence: 99%
See 1 more Smart Citation